Erythematous nodes, urticarial rash and arthralgias in a large pedigree with NLRC4‐related autoinflammatory disease, expansion of the phenotype. (8th December 2016) - Volker‐Touw, C.M.L.; de Koning, H.D.; Giltay, J. C.; de Kovel, C.G.F.; van Kempen, T.S.; Oberndorff, K.M.E.J; Boes, M.L.; van Steensel, M.A.M.; van Well, G.T.J.; Blokx, W.A.M.; Schalkwijk, J.; Simon, A.; et al.
Abstract : Linked Comment: Barzilai and Cohen. Br J Dermatol 2017; 176 :18–19 .